2016
DOI: 10.1007/s00402-016-2533-6
|View full text |Cite
|
Sign up to set email alerts
|

Is the prognosis the same for periprosthetic joint infections due to Staphylococcus aureus versus coagulase-negative staphylococci? A retrospective study of 101 patients with 2-year minimum follow-up

Abstract: III, retrospective case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This notion of an ongoing natural selection of more hostile CoNS is further supported by previously unexpected findings concerning the non-inferiority of MRSA outcomes when compared to CoNS sequelae in a small series of PJIs in contemporary literature [47,55,56]. This is in contrast to prior literature that found a greater incidence of treatment susceptibility in CoNS, such as Staphylococcus epidermidis, than in MRSA [26,57,58].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This notion of an ongoing natural selection of more hostile CoNS is further supported by previously unexpected findings concerning the non-inferiority of MRSA outcomes when compared to CoNS sequelae in a small series of PJIs in contemporary literature [47,55,56]. This is in contrast to prior literature that found a greater incidence of treatment susceptibility in CoNS, such as Staphylococcus epidermidis, than in MRSA [26,57,58].…”
Section: Discussionsupporting
confidence: 64%
“…This is in contrast to prior literature that found a greater incidence of treatment susceptibility in CoNS, such as Staphylococcus epidermidis, than in MRSA [26,57,58]. Whereas pathogens such as MRSA have been traditionally feared as treatment resistant, with investigators recommending early and more invasive and aggressive intervention [38], the tendency toward rapid biofilm formation and antibiotic resistance acquisition in CoNS makes their behavior in the PJI setting fairly similar at present [55,56]. Our data supports this notion of an increasingly recalcitrant family of bacteria.…”
Section: Discussionmentioning
confidence: 71%
“…CoNS and SA are often responsible for PJI and are implicated in approximately 25% of cases [23e25]. Although SA has a higher intrinsic virulence than CoNS [26], Murgier et al [27] reported that the healing rate of SA PJI was similar to that of CoNS PJI, and that both must be treated with same degree of rigor. In addition, a recent study by Cunningham et al [28] showed that CoNS was the most common organism in PJI and was associated with an increased risk of additional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulase-negative staphylococci (CoNS) are a hard-to-treat group of microorganisms in relation to implanted foreign materials, due to a high rate of methicillin resistance and biofilm formation[1]. In recent years, the incidence of infections with CoNS has increased[2,3]. Periprosthetic joint infection (PJI) is a devastating complication after hip and knee arthroplasty that occurs in 1%-2% of patients[4].…”
Section: Introductionmentioning
confidence: 99%